The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/jbl.12044
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐Organizational Learning in Supply Chains: A Focus on Logistics Service Providers and Their Customers

Abstract: T he learning process between supply chain entities is explored from the perspective of senior third-party executives. Through grounded theory, a theoretical framework emerged that extends our understanding of learning within a supply chain by identifying the major constructs and learning stages comprising the basic social process of inter-organizational learning. This framework provides significant insights into the complex process employed in a supply chain to share, disseminate, and store information; co-cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 89 publications
2
35
0
5
Order By: Relevance
“…We also observed "interorganizational learning" taking place throughout the innovation process. This observation is consistent with the finding of Manuj et al (2014), Su et al (2011), andLee et al (2011) on the need to include not only customers but also other stakeholders such as suppliers in the logistics innovation process. The antecedents of logistics innovation identified by Grawe (2009) in a systematic review of logistics journals were also found in the case of On-site Shop.…”
Section: Implications For Theorysupporting
confidence: 92%
See 2 more Smart Citations
“…We also observed "interorganizational learning" taking place throughout the innovation process. This observation is consistent with the finding of Manuj et al (2014), Su et al (2011), andLee et al (2011) on the need to include not only customers but also other stakeholders such as suppliers in the logistics innovation process. The antecedents of logistics innovation identified by Grawe (2009) in a systematic review of logistics journals were also found in the case of On-site Shop.…”
Section: Implications For Theorysupporting
confidence: 92%
“…Moreover, the centralized organization played a central role for “interorganizational learning” (Manuj et al. ) from the beginning of the innovation process.…”
Section: Generative Mechanisms Of Observed Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…; Manuj et al. ). The interviews, which were conducted over a six‐month period, lasted from 40 and 60 min; interviews were audiotaped and transcribed verbatim.…”
Section: Study 1: Inductively Framing the Researchmentioning
confidence: 98%
“…This pattern reflects the need for organizational capacity to process substantial volumes of information with high levels of ambiguity. The knowledge-based view (e.g., Grant 1996) and organizational learning (Levinthal and March 1993;Manuj et al 2014) identify knowledge as a critical resource that is created and dispersed across individuals in an organization. An important organizational task is to integrate individuals' existing specialized knowledge in ways that foster the development of new knowledge (Grant 1996;Zollo and Winter 2002).…”
Section: Theoretical Interpretation Of Links Between Integration Requmentioning
confidence: 99%